The Impact of Cultural Distance and Country Risk on the Entry Mode Choice of Chinese Multinational Enterprises - Maguire, Remy (2012)
In the decade since China gained membership to the World Trade Organisation the number of Chinese multinational enterprises (MNEs) has risen dramatically. Yet despite foreign direct investment (FDI) and entry mode choice being among the most researched topics in the field of international business, there are relatively few studies that apply this knowledge to the case of Chinese firms. In order to contribute to this small but growing body of literature, this study analyses the determining factors of the entry mode choice between wholly-owned subsidiary (WOS) and joint-venture (JV). The subject matter is addressed using an empirical, explanatory approach which follows the process of deduction throughout. Building on two leading theoretical perspectives, the institution and resource-based views, hypotheses are developed to test the impact of cultural distance and country risk upon the entry mode choice of Chinese firms. Through the collection of secondary data, a sample of 33 Chinese companies and 87 entry mode decisions were observed and subjected to binomial logistic regression analyses. The study, employing data from 2009-2011, represents the most up to date in the field of research. To the extent that the results depart from conventional wisdom, cultural distance and country risk were shown not exert a significant influence on entry mode choice. The results do however appear to give further credence to the view that Chinese firms exhibit unique characteristics that differ substantially from their counterparts in more developed countries. In this respect the development of the institution-based view will hold substantial value to both theoreticians and practitioners of Chinese international business (IB).